METODE PEMBELAJARAN QUANTUM LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MI: METODE PEMBELAJARAN QUANTUM LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MI - Anggi Apriliani; Umi Kalsum Kalsum; Tarmiji Siregar (Al Ittihadu, 2025)
In the learning process starting from the madrasah Ibtidaiyah level, you can choose the right learning strategy because it is the key to success for students in learning, student activity is something that every teacher wants to do, therefore Quantum Learning is a learning method that uses a lot of senses such as sight. , smell, taste, touch, and research subjects in every school, teachers are required to apply learning media to each theme or subject that is delivered besides that Quantum Learning is able to improve learning outcomes that are active and creative students.